Pendidikan Formal Anak Pada Keluarga Petani Ikan Di Desa Pudak Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi Provinsi Jambi - Asmaida Asmaida; Arosidin Arosidin (Universitas Batangahari Jambi, 2021)
Abstrack. The study aims to describe the distribution of children's formal education levels to fish farming families, and the perception of fish farming families to the formal education of children, as well as analyze the level of formal education of children of fish farmers in Pudak Village, Kumpeh Ulu District, Muaro Jambi Province. Data analysis uses descriptive methods both qualitatively and quantitatively and multiple linear regression analysis. The results showed that the distribution of the level of formal education of fish farmers' children in Pudak Village of Kumpeh Ulu Subdistrict was uneven, the percentage in the lower education category (elementary and junior high) amounted to 48.40%, the moderate education category (SLTA) by 38.71% and the higher education category (D3 and S1) by 12.89%. Farmers perceive that formal education is important for children, through education can expand thinking and knowledge as a provision for children's lives in the future so that they have a decent job and their lives are better than the conditions of their parents. Of the six factors (age of the head of the family, the education of the head of the family, the number of dependents of the head of the family, the income of the head of the family, the distance of the educational facilities, the sex of the child) included in the model, there are two factors that affect the level of formal education of the child in the fish farming family, namely family income and distance of residence with educational facilities. The coefficient of determination of 85.5% which means that both factors as free variables are able to explain the child's formal education level as a non-free variable and 14.5% cannot be explained by the model but is explained by other factors outside the model.Keywords: Formal Education, Children, Fish Farmers